The prejudicial settlement in civil and family matters, as a procedure requirement to access a jurisdictional process (Revista de Investigaciones Universidad del Quindío, 2021)
The predisposition of people to maintain a litigious mentality and the lack of dissemination of the various procedures that exist to resolve conflicts, has caused the parties to choose to resolve their disagreements in the traditional way, that is, through the jurisdictional process. However, the critical situation that prevails within the courts for the administration of justice is unknown to anyone. The increase in the index in the promotion of lawsuits that are filed daily by individuals, in order to resolve their legal disagreements in the civil and family sphere, has had a negative impact on the resolution of conflicts through jurisdictional channels. Situation that becomes notorious in the delay and delay of the processes that are urged in order to obtain a prompt and expeditious justice. Faced with such a collapse, time and necessity have forced us to look for various options or alternatives that put an end to conflicts of this nature, in an efficient, effective, simple, fast and economic way. This article is based on the analysis of the need to materialize the constitutional mandate to access an alternative justice through the implementation of a mandatory pretrial conciliation instance in civil and family matters. Procedure prior to the process, the objective of which will be to provide a genuine possibility of resolving conflicts of a civil and family nature, as well as shortening the deadlines for their resolution, which must be presided over by expert conciliatory officials.
Keywords: alternative dispute resolution mechanisms; access to the justice; alternative justice; prejudicial conciliation; jurisdictional process